Upper mantle seismic wave velocities in the Hindukush region (MAUSAM, 1967)
Gutenberg's method has been applied for the determination of the seismic wave velocities and their variations with depth in the upper part of the upper mantle below the hindukush mountains. Data from fifty earthquakes occurring at various depths in the Hindukush region have been utilised. The results confirm the existence of a low velocity layer for S-waves at a depth of about 160km below the surface. The S-velocity decreases slowly from a value of 4.5 km{sec at a depth of 65 kin to a value of 4.4, km/sec at a depth of 160 km after which it rises again reaching value of 4,. 52 km{sec at a depth of 225km. No such velocity minima is, however, discernible in the case of P.waves. The velocity of P-waves appears to remain nearly constant at 8 km/sec up to a depth of 160km. It then rises steeply up to a depth of 200 km after which the velocity gradient decreases. The value of Poisson's ratio just below the Mohorovicic discontinuity in this region works out to be 0.26. This value increases steadily to 0.29 upto a depth of 225 km and then attains a constant value.